The Church and the media : evangelism or manipulation - Bogešić, Robert (Array, 2019)
Can the media kill faith? What is the relationship between the Church and the media? What should be the relationship between these two subjects that are oriented for large audiences? Should there even be a relationship between them? What is the character of the subjects building this relationship? Should the media have any sort of relationship with the Church, and vice-versa? These are some of the questions that arise when we think about the relationship between the media and churches. Both subjects have a common element in their activities: a relationship with a large number of users. Even more so, both the churches and the media need to build mutual relationships which will contribute to improving and achieving their interests and to developing various groups as well as individuals that they are targeting. On the one hand, the Church is tasked with proclaiming the Good News to the nations, while the media in their work try to communicate various information to as many users. In this way, both the church and the media meet their function of reaching massive audiences. Can churches use some of these media in fulfilling its task, or can some of the media use churches for promoting their products? These are questions which are sometimes burdensome but are primarily meant to enrich the fields of both subjects’ activities.